PENGARUH KUALITAS PRODUK DAN SISTEM INFORMASI PEMASARAN TERHADAP PENINGKATAN PERMINTAAN DI PT. WAHANA TRANS LESTARI MEDAN - Bagus Handoko (JRMB (Jurnal Riset Manajemen & Bisnis), 2021)
Every company must have a desire to be successful in marketing all products, both goods and services. This success can be achieved by setting the cost price correctly. Product is one element of the marketing mix in addition to the other three elements (price, distribution, and promotion). Marketing information system is a set of information elements that have been prepared, arranged systematically to become a complete data in order to fulfill / support the activities of the organization and managers in general. From the description above, the authors formulate the problem: "The influence of product quality and marketing information systems on increasing demand at PT Wahana Trans Lestari Medan". Based on the value of the F test, it is obtained that Fcount (Fh) = 16.945 this value is then consulted with Ftable, based on the dk of the numerator = k and dk of the denominator = (n-k-1). Then obtained F table = 3.30. These results indicate that the calculated F is greater than the F table, which is 16.945 3.30, so the multiple correlation coefficient tested is significant. It can be seen that the percentage of influence between the independent variable (x1) is product quality and the independent variable (x2) is the marketing information system with the dependent variable (y) on the increase in demand at PT. Wahana Trans Lestari Medan is 51.4% while 48.6% is influenced by other factors. It takes a certain section that specifically manages everything regarding information to serve the information needs of operating activities so that a truly effective specialization of the information section will be created. Plans for the development of an integrated marketing information system in the future need to be realized immediately and the existing computer capacity fully utilized, this can be beneficial for increasing market demand.